Operação urbana Faria Lima - Oliveira Filho, Caio Augusto Barbosa de (2007)
This project analyzes the results of the Urban Operation Implantation in the city of São Paulo starting from the calculation of the densification and also from the valorization suffered by the perimeter held by this operation, since 1995 until 2004. This calculation is based on the data organization obtained from the City hall from São Paulo City (PMSP), Official gazette of City (DOM), City Planning Department (Sempla) and Municipal Company of Urbanization (Emurb) Not only is this analysis based on the conceptualization of urban project and urban operation, but also on comments made regarding positive examples of established international urban operations already done. Besides there are other experiences implanted in the city of São Paulo, trying to disclose the aspects that had contributed and/or compromised the attainment of its effective results.